Pengaruh Fasilitas Live Music Dan Harga Terhadap Keputusan Pembelian Di Warunk Nonstop - Irfan Aji Wiranata; Salim Siregar (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to examine and analyze the effect of Live Music Facility and Price on the Purchase Decision of a case study on Instagram followers @warunknonstop. This study uses quantitative methods with descriptive and verification approaches. The sample in this study was taken from the number of Instagram followers which amounted to 1,708 using the Slovin formula with a total sample of 273 followers. The sampling technique used is purposive sampling. This research uses path analysis technique. The results of this study indicate that there is a correlation between Live Music Facilities and Prices. Partially Live Music Facility has a significant effect on Purchase Decisions as well as Price has a significant effect on Purchase Decisions. Simultaneously Live Music Facility and Price have a significant effect on Purchase Decision by 49.7% while the remaining 50.4% is influenced by other variables not examined. Keyword : Live Music Facility, Price and Purchase Decision.